2022
DOI: 10.3390/jcm11164859
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Observational Study Assessing the Clinical Outcomes of a Novel Implant System with Low-Speed Site Preparation Protocol and Tri-Oval Implant Geometry

Abstract: A novel, biologically friendly implant concept system introduces low-speed (50 rpm) site preparation instruments used without irrigation and a tri-oval, tapered implant designed to reduce stress on cortical bone without sacrificing mechanical stability. This retrospective, observational, multicenter study (clinicaltrials.gov NCT04736771) collected data from consecutive patients treated with at least one novel concept system implant to evaluate clinical outcomes after 1 year in function. The primary endpoint wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…From a clinical perspective, the omission of cervical threads did not enhance esthetic performance as compared to a more traditional, round implant design [36]. Similarly, no major advantage with respect to marginal bone level change was described for implants with a tri-oval [37] or a triangular [38] design.…”
Section: Introductionmentioning
confidence: 84%
“…From a clinical perspective, the omission of cervical threads did not enhance esthetic performance as compared to a more traditional, round implant design [36]. Similarly, no major advantage with respect to marginal bone level change was described for implants with a tri-oval [37] or a triangular [38] design.…”
Section: Introductionmentioning
confidence: 84%
“…Another problem is the definition of success criteria in clinical studies [3][4][5]. In a number of studies, only those implants that had reached at least the phase of the prosthetic treatment are counted as lost.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the new protocol involves the use of a single drill (‘osseodirector’), an implant‐specific single‐use bone shaping instrument (‘osseoshaper’) followed by placement of the implant with a novel tri‐oval connection, which is co‐packaged with the bone shaping instrument. A short‐term retrospective study across numerous clinicians reported preliminary data on the successful use of the novel N1 System 7 . The authors reported minimal bone remodeling, a high implant survival rate, and improved clinician and patient satisfaction 7 .…”
mentioning
confidence: 99%
“…A short‐term retrospective study across numerous clinicians reported preliminary data on the successful use of the novel N1 System 7 . The authors reported minimal bone remodeling, a high implant survival rate, and improved clinician and patient satisfaction 7 . The purpose of this clinical report was to describe the successful management of a male patient with a history of coagulopathy who was rehabilitated with complete arch fixed implant‐supported prostheses with immediate loading using the novel implant design and drilling protocol.…”
mentioning
confidence: 99%